2018
DOI: 10.12669/pjms.344.14513
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Plasma N-terminal Pro-brain Natriuretic Peptide and D‑dimer on the Prognosis of Patients with Acute Cerebral Infarction

Abstract: Objective:To investigate the effects of levels of D-dimer and N-terminal pro-brain natriuretic peptide (NT-pro BNP) on the prognosis of patients with acute cerebral infarction.Methods:One hundred and twenty-four patients with acute cerebral infarction who were admitted to the hospital between July 2014 and July 2016 were selected as the observation group; 100 normal people who had health examination in the center of physical examination of our hospital were selected as the control group. The levels of D-dimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Compared with the control group, the level of NT-proBNP in the acute ischemic stroke group was higher (WMD = 1600.92, 95% CI = 607.00-2594.84, p = 0.002, I 2 = 99%, p-value of heterogeneity <0.00001). Additionally, a significant difference in NT-proBNP was found between patients in the 2018 [9] proBNP infarction 3). We believe that this result was found due to the small number of articles studied.…”
Section: Pooled Results From Literature-based Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the control group, the level of NT-proBNP in the acute ischemic stroke group was higher (WMD = 1600.92, 95% CI = 607.00-2594.84, p = 0.002, I 2 = 99%, p-value of heterogeneity <0.00001). Additionally, a significant difference in NT-proBNP was found between patients in the 2018 [9] proBNP infarction 3). We believe that this result was found due to the small number of articles studied.…”
Section: Pooled Results From Literature-based Meta-analysismentioning
confidence: 99%
“…(3) exposure: (f) ascertainment of exposure, (g) the same method of ascertainment for cases and controls, and (h) the non-response rate. [9] ☆ ☆ ☆ ☆ ☆ ☆ ☆ 7…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of Ddimer suggests that it is related to thrombotic diseases caused, and it illustrates the enhancement of brinolytic activity. Existing studies generally support that the increase of D-dimer is a risk factor for cerebral infarction, and it has predictive signi cance for the course of the disease [19][20][21]. Studies have shown that cholesterol carried by LDL is prone to accumulate on the walls of blood vessels and arteries, forming unstable soft plaques, which blocks the cerebral artery and causes a cerebral infarction [22][23][24].…”
Section: Discussionmentioning
confidence: 99%